Thinking styles and academic stress coping among Chinese secondary school students. Issue 8 (14th September 2017) - Yuan, Wei; Zhang, Li-Fang; Fu, Mingchen
Abstract: This study investigated the predictive power of thinking styles for academic stress coping. Participants were 563 (280 males, 275 females, 8 gender unspecified) secondary school students in grades 7 through 12 from mainland China. Thinking styles were measured using the Thinking Styles Inventory-Revised II which was based on the theory of mental self-government. Coping strategies were measured by the COPE-Revised, which was derived from Carver's COPE (1989). Results showed that thinking styles had statistically significant predictive power for academic stress-coping strategies beyond age and gender, largely in the expected directions. Theoretical implications for research on intellectual styles and coping are discussed; and some practical implications for school teachers and students are proposed.